f-6-3f+1=13

Simple and best practice solution for f-6-3f+1=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f-6-3f+1=13 equation:


Simplifying
f + -6 + -3f + 1 = 13

Reorder the terms:
-6 + 1 + f + -3f = 13

Combine like terms: -6 + 1 = -5
-5 + f + -3f = 13

Combine like terms: f + -3f = -2f
-5 + -2f = 13

Solving
-5 + -2f = 13

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -2f = 13 + 5

Combine like terms: -5 + 5 = 0
0 + -2f = 13 + 5
-2f = 13 + 5

Combine like terms: 13 + 5 = 18
-2f = 18

Divide each side by '-2'.
f = -9

Simplifying
f = -9

See similar equations:

| 17-x=1.3(15)+6 | | 6/-3z=10 | | 4.5=-0.5(x-7.1) | | x-(2-x)=-2x(-2x-4) | | log125x=1/3 | | 2(2x)-12=2x-4 | | 9x-20+12+60=180 | | 6=7a+6a | | (3/(x-2))-(2/x)0 | | (3/(x-2))-(2/x) | | x-45=2.3 | | 6x-2(4x+5)=x-8 | | 4-3(1-2x)= | | x^3+4x^2-6=0 | | 7+2(3x+5)= | | 2(3x-9)-10=3x-13 | | 1.2x+10=1.4x+54 | | 3x-13=y-4 | | 11x^2+33x+12=0 | | F(x)=(x-3)(x-4i)(x-4i) | | 672=12(-7x-21) | | 63-7x=-3-189 | | 5x+5x+2+7=6x+4+3 | | 36+9264= | | -3(10+6)=-66 | | 7x=169 | | 2cos^2x+sinx+1=0 | | -3(10+6x)=-66 | | -4x+8=x+7 | | x^4-4x^3+30x^2-100x+125=0 | | -1+15x=180 | | -x+6y=11+x |

Equations solver categories